IMPLEMENTATION OF THE SPIRAL METHOD FOR ANALYZING AND DESIGNING FINANCIAL INFORMATION SYSTEMS AND FINANCIAL ARCHIVES FOR CASHIER FINANCIAL MANAGEMENT SECTION (CASH INFORMATION REPLACEMENT) - Muammar Khadapi (Yayasan Kita Menulis, 2023)
This title is backgrounded by financial management employees in the PT Telekomunikasi Indonesia.Tbk Cooperative in the form of Application.There are many problems happened such as the data did not saved well and the financial data was mixed with the other archive. The purpose of this research is to build a cashier application system which will enumerate employees in its financial arrangement, both income and from the cooperative and then become a file which is computerized will facilitate the employees. The methods which is used in this application development method is Spiral. It is the systematic approach and sequentially to software, start from users’ specification necessary until the planning, modeling, construction, and deployment. After analyzing the problems that occur then made the improvement to the current problem by build an application that supports web-based financial processes.